[Journal of Captain Cook's third voyage] - Law, John (Adam Matthew Digital, 1779)
Ms. journal of Captain Cook's third voyage by John Law on board Discovery, 16 Jan.-1 May 1779; includes details of events on Hawaii at the time of the death of Captain Cook